Visualization of Muslims in Video Game as a Leading Image of Islam for Society - Albar, Deni; Nurimbono, Citra (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Economically, the global game market generates a profit of around IDR 2.2 trillion in 2020. Half of this revenue comes from the Asia Pacific region. Games can no longer be underestimated as a form of communication technology media that can affect human life. In video games there are messages conveyed to the players, these messages can be ideological, political, economic, social and cultural. One of the messages in the game world that is interesting to study is the image of Muslims in the world of games developed by developers from the West or Europe that display cultural bias, especially since the 9/11 incident in the United States until its development in 2022. This study aims to find a conceptual formulation in the application of imagery of a religion, especially Islam in game media. This research is oriented towards explanations in anticipation of religious phenomena/symptoms in supporting the process of its application in the game world as a technological medium. The method used in this research is descriptive qualitative research with the method of library data. This research was conducted by examining the visual representation of visual symbols of the Islamic religion in various video games, especially video games developed by western developers, then associating them with the activities in the game. In this study the description uses the facts from the data obtained as they are. The results of this research are expected to show the formulation of the concept in representing Islam in the game world and become the correct reference in its application. The results show that in the early 2000s, information about Muslims was minimal so that Muslim visualizations were often used as antagonistic positions and tended to be people from the Middle East, and over time, up to 20 years later, Muslim positions could be positioned better. The conclusion is that Islam is a religion for all races, therefore it is not correct to describe Islam only to one race. Hijab is the most appropriate way to visually represent Muslim women in games, or keffiyeh / shemagh even though it is a cultural artefact from the Arabs, but its existence has also spread to other Islamic countries and is firmly entrenched in the minds of the general public as a hallmark of Muslims. so that keffiyeh/shemagh can become one of Islamic identities, even though it is not quite right.